Evaluation of Psychosocial Pathways to Family Adaptation of Chinese Patients With Liver Cancer Using the McCubbin's Family Resilience Model - Mao, Shirou; Lu, Huijuan; Zhang, Yuxia; Yu, Jingxian; Li, Xiaorong; Peng, Jian; Liang, Yan (Frontiers in Psychiatry, 2021)
Background and aim: With the prolonged survival time of patients with liver cancer, these families may face tremendous pressure and development dilemmas that can easily lead to family adaptation crises. Correspondingly, family adaptation crises adversely affect the quality of life of patients and family members. Basing on McCubbin’s resilience model of family stress, adjustment, and adaptation, and considering the key factors affecting family resilience upon literature review, this study constructed a model of influencing factors of family adaptation in Chinese liver cancer patients then verified and revised it. Methods: This cross-sectional study was conducted between August and December 2020. Using convenience sampling, we selected 265 liver cancer families in liver tumor center of a teaching hospital affiliated with a university in Shanghai, China. Data from 252 patients with liver cancer and their caregivers were used to identify the factors and pathways associated with family adaptation. The relationships were modeled using structural equations. Results: A total of 265 liver cancer families participated in the survey, and 252 valid questionnaires were returned, with a response rate of 95.09%. The pathway regression coefficients of six factors (family burden, individual resilience, family problem-solving and coping, inner family support, outer family social support, and family function) in the model were found to be statistically significant (P<0.05), indicating that all of them were significantly associated with family adaptation. Among them, inner family support, outer family social support, and family function were direct influencing factors, while the others were indirect. The path coefficients of the total effect of the determinants on family adaptation, from largest to smallest, were as follows (from largest to smallest): individual resilience (0.562), family function (0.483), outer family social support (0.345), family burden (- 0.300), inner family support (0.293), family problem-solving and coping (0.127). Conclusions: Our findings suggest that clinical nurses should not only pay particular attention to direct influencing factors, take strategies to strengthen the overall family function, encourage them to utilize inner family and outer family social support, but should also consider indirect influence factors, focus on the key role of the individual, and promote their personal and family coping ability.